A damage model for volcanic edifices: Implications for edifice strength, magma pressure, and eruptive processes. Issue 1 (18th January 2015) - Carrier, Aurore; Got, Jean‐Luc; Peltier, Aline; Ferrazzini, Valérie; Staudacher, Thomas; Kowalski, Philippe; Boissier, Patrice
Abstract Monitoring of large basaltic volcanoes, such as Piton de la Fournaise (La Réunion Island, France), has revealed preeruptive accelerations in surface displacements and seismicity rate over a period of between 1 h and several weeks before magma reaches the surface. Such eruptions are attributed to ruptures of pressurized magma reservoirs. Elastic models used to describe surface deformation would assume that accelerations in surface deformation are due to increases in reservoir pressure. This assumption requires changes in magma or pressure conditions at the base of the magma feeding system that are unrealistic over the observed timescale. Another possible cause for these accelerations is magma pressure in the reservoir weakening the volcanic edifice. In the present study, we modeled such weakening by progressive damage to an initially elastic edifice. We used an incremental damage model, with seismicity as a damage variable with daily increments. Elastic moduli decrease linearly with each damage increment. Applied to an initially elastic edifice with constant pressure at the base of the system, this damage model reproduces surface displacement accelerations quite well when damage is sufficient. Process dynamics is controlled by the damage parameter, taken as the ratio between the incremental rupture surface and the surface to be ruptured. In this case, edifice strength and magma reservoir pressure decrease with decreasing elastic moduli, whereas surface displacement accelerates. We discuss the consequences of pressure decreases in magma reservoirs.